HAWC study of the ultra-high-energy spectrum of MGRO J1908+06 - Albert, Andrea; Alfaro, R.; Alvarez, C.; Alvarez, J. D.; Angeles Camacho, J. R.; Arteaga-Velazquez, J. C.; Avila Rojas, D.; Solares, H. A. Ayala; Babu, R.; Belmont-Moreno, E.; Brisbois, C.; Caballero-Mora, K. S.; et al. (The astrophysical journal, 2022)
We report TeV gamma-ray observations of the ultra-high-energy source MGRO J1908+06 using data from the High Altitude Water Cherenkov Observatory. This source is one of the highest-energy known gamma-ray sources, with emission extending past 200 TeV. Modeling suggests that the bulk of the TeV gamma-ray emission is leptonic in nature, driven by the energetic radio-faint pulsar PSR J1907+0602. Depending on what assumptions are included in the model, a hadronic component may also be allowed. Using the results of the modeling, we discuss implications for detection prospects by multi-messenger campaigns.